Potential modernity and emancipation from the patriarchal sex-gender system. Fictional exchanges between Bolívar Echeverría and Peggy R. Sanday - CALVO RIVERA, Érika (Utopía y Praxis Latinoamericana, 2025)
This text engages in a dialogue between Bolivar Echeverria’s notion of «essential modernity» and Peggy Reeves Sanday’s analysis of the origins of sexual inequality. For Echeverria, modernity’s potentiality lies in the promise of abundance; while for Sanday, the cause of male dominance is rooted in the hostilities of the natural world. The fictional exchange between these two allows me to argue that the overcoming of civilizational scarcity, which Echeverria identifies as the essence of modernity, could also be seen as a feminist promise for overcoming the patriarchal sex-gender system. This constitutes a novel argument with which I aim to deepen the debate on the link between modernity and feminism and expand, from a gender perspective, the horizons of possibility of the alternative modernity advocated by Bolívar Echeverría.